Implementasi Prinsip Non Refoulement dalam Kebijakan Penanganan Pengungsi Asing di Indonesia: Perspektif Hukum Internasional dan Nasional - Wahyudi, Wahyudi (Pusat Analisis Keparlemenan Badan Keahlian Setjen DPR RI, 2025)
This article examines the implementation of the principle of non-refoulement in Indonesia’s policy on foreign refugees from both international and national legal perspectives. As a non-signatory to the 1951 Refugee Convention and its 1967 Protocol, Indonesia is not bound by their formal obligations; however, the principle of non-refoulement remains relevant as part of customary international law. The study employs a normative legal research method, analyzing primary and secondary legal sources, including international instruments, national regulations, and policy practices. Findings indicate that while Indonesia has taken initial steps through Presidential Regulation No. 125 of 2016, the absence of a dedicated refugee law, inconsistent inter-agency coordination, limited administrative capacity, and negative public perceptions hinder effective implementation of non-refoulement. Furthermore, refugee detention conditions and ad hoc decision-making often fail to meet international human rights standards. The article concludes that harmonizing international norms with domestic law is essential for a more structured and humane refugee protection framework. Recommendations include enacting specific legislation on refugees, enhancing institutional coordination, improving detention facilities, and increasing public awareness. With stronger political will and commitment to humanitarian values, Indonesia can strengthen its role as a responsible transit country and contribute meaningfully to global refugee protection efforts.